Survey into the Characteristics, Working Conditions and Deficiencies of Turkish Seafood Processing Firms - EYGİ ERDOĞAN, BİRSEN (CENTRAL FISHERIES RESEARCH INST, 2014)
Since Turkey is an important seafood supplier to the world market, working conditions and deficiencies of Turkish seafood processing firms were surveyed. Inadequacy of employee education was the main barrier of HACCP implementation. Unpredictable raw material availability, price of raw material, defective audit policy of the government, lack of information transfer from the universities, excessive bureaucracy, difficulty of employee education, excessive use of glazing and additives by rivals, tax rates, ignorance of the inspectors, difficulty to getting credits were the factors, complicating productivity. The domestic trade barriers were the unbounded seafood imports, antipathy of Turkish consumers against seafoods, price of seafood, inadequacy of cold chain conditions. Instability of foreign exchange, undersell of seafoods in the global market, instability of raw material quality, uninformative attitude of the government about foreign supports, communication problem with the buyers, excessive bureaucracy, obscurity of Turkish seafoods products were the barriers, complicating foreign trade. As an important seafood supplier, improving working conditions and elimination of deficiencies are essential for Turkey. Turkish government has to inform processing firms about the available supports and opportunities of foreign trade. Making provisions for distortions in credit market and providing convenience to get credit might be the other tasks of the government.
Keywords: Seafood; survey; processing firm; import; export; CONSUMPTION; INDUSTRY; QUALITY